Speckle imaging excludes low-mass companions orbiting the exoplanet host star trappist-1 - Howell, Steve B; Everett, Mark E; Horch, Elliott P; Winters, Jennifer G; Hirsch, Lea A; Nusdeo, Dan; Scott, Nicholas J (The Astrophysical Journal, 2016)
We have obtained the highest-resolution images available of TRAPPIST-1 using the Gemini-South telescope and our speckle imaging camera. Observing at 692 and 883 nm, we reached the diffraction limit of the telescope providing a best resolution of 27 mas or, at the distance of TRAPPIST-1, a spatial resolution of 0.32 au. Our imaging of the star extends from 0.32 to 14.5 au. We show that to a high confidence level, we can exclude all possible stellar and brown dwarf companions, indicating that TRAPPIST-1 is a single star. © 2016. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; stars: imaging; stars: individual (TRAPPIST-1, 2MASS J23062928-0502285)

Stellar companions to the exoplanet host stars HD 2638 and HD 164509 - Wittrock, Justin M; Kane, Stephen R; Horch, Elliott P; Hirsch, Lea A; Howell, Steve B; Ciardi, David R; Everett, Mark E; Teske, Johanna K (The Astronomical Journal, 2016)
An important aspect of searching for exoplanets is understanding the binarity of the host stars. It is particularly important, because nearly half of the solar-like stars within our own Milky Way are part of binary or multiple systems. Moreover, the presence of two or more stars within a system can place further constraints on planetary formation, evolution, and orbital dynamics. As part of our survey of almost a hundred host stars, we obtained images at 692 and 880 nm bands using the Differential Speckle Survey Instrument (DSSI) at the Gemini-North Observatory. From our survey, we detect stellar companions to HD-2638 and HD-164509. The stellar companion to HD-2638 has been previously detected, but the companion to HD-164509 is a newly discovered companion. The angular separation for HD-2638 is 0.512±0 002 and for HD-164509 is 0.697 0. 00 ' 2. This corresponds to a projected separation of 25.6±1.9 au and 36.5±1.9 au, respectively. By employing stellar isochrone models, we estimate the mass of the stellar companions of HD-2638 and HD-164509 to be 0.483±0.007-Me and 0.416 0.007 M, respectively, and their effective temperatures to be 3570±8K and 3450±7K, respectively. These results are consistent with the detected companions being late-type M dwarfs. © 2016. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; peer-reviewed; planetary systems; stars: individual (HD 2638, HD 164509); techniques: high angular resolution

Speckle imaging characterization of radial velocity exoplanet systems - Dalba, Paul A.; Kane, Stephen R.; Howell, Steve B; Horch, Elliott P; Li, Zhexing; Hirsch, Lea A.; Burt, Jennifer; Brandt, Timothy D.; Močnik, Teo; Henry, Gregory W. (Astronomical Journal, 2021)
We conducted speckle imaging observations of 53 stellar systems that were members of long-term radial velocity (RV) monitoring campaigns and exhibited substantial accelerations indicative of planetary or stellar companions in wide orbits. Our observations were made with blue and red filters using the Differential Speckle Survey Instrument at Gemini-South and the NN-Explore Exoplanet Stellar Speckle Imager at the WIYN telescope. The speckle imaging identifies eight luminous companions within 2" of the primary stars. In three of these systems-HD 1388, HD 87359, and HD 104304-the properties of the imaged companion are consistent with the RV measurements, suggesting that these companions may be associated with the primary and the cause of the RV variation. For all 53 stellar systems, we derive differential magnitude limits (i.e., contrast curves) from the imaging. We extend this analysis to include upper limits on companion mass in systems without imaging detections. In 25 systems, we rule out companions with masses greater than 0.2 M⊙, suggesting that the observed RV signals are caused by late-M dwarfs or substellar (potentially planetary) objects. On the other hand, the joint RV and imaging analysis almost entirely rules out planetary explanations of the RV signal for HD 19522 and suggests that the companion must have an angular separation below a few tenths of an arcsecond. This work highlights the importance of combined RV and imaging observations for characterizing the outer regions of nearby planetary systems. © 2021 Institute of Physics Publishing. All rights reserved.
Keywords: dept.phy; peer-reviewed

Assessing the effect of stellar companions from high-resolution imaging of Kepler objects of interest - Hirsch, Lea A.; Ciardi, David R.; Howard, Andrew W.; Everett, Mark E.; Furlan, Elise; Saylors, Mindy; Horch, Elliott P.; Howell, Steve B.; Teske, Johanna; Marcy, Geoffrey W. (The Astronomical Journal, 2017)
We report on 176 close (<2″) stellar companions detected with high-resolution imaging near 170 hosts of Kepler Objects of Interest (KOIs). These Kepler targets were prioritized for imaging follow-up based on the presence of small planets, so most of the KOIs in these systems (176 out of 204) have nominal radii <6 . Each KOI in our sample was observed in at least two filters with adaptive optics, speckle imaging, lucky imaging, or the Hubble Space Telescope. Multi-filter photometry provides color information on the companions, allowing us to constrain their stellar properties and assess the probability that the companions are physically bound. We find that 60%-80% of companions within 1″ are bound, and the bound fraction is >90% for companions within 0.″5; the bound fraction decreases with increasing angular separation. This picture is consistent with simulations of the binary and background stellar populations in the Kepler field. We also reassess the planet radii in these systems, converting the observed differential magnitudes to a contamination in the Kepler bandpass and calculating the planet radius correction factor, X R = R p(true)/R p(single). Under the assumption that planets in bound binaries are equally likely to orbit the primary or secondary, we find a mean radius correction factor for planets in stellar multiples of X R = 1.65. If stellar multiplicity in the Kepler field is similar to the solar neighborhood, then nearly half of all Kepler planets may have radii underestimated by an average of 65%, unless vetted using high-resolution imaging or spectroscopy. © 2017. The American Astronomical Society. All rights reserved.
Keywords: binaries: visual; dept.phy; peer-reviewed; planets and satellites: detection; planets and satellites: fundamental parameters; techniques: high angular resolution; techniques: photometric

A comparison of spectroscopic versus imaging techniques for detecting close companions to kepler objects of interest - Teske, Johanna K; Everett, Mark E; Hirsch, Lea A; Furlan, Elise; Horch, Elliott P; Horch, Elliott P; Howell, Steve B; Ciardi, David R; Gonzales, Erica J; Crepp, Justin R (The Astronomical Journal, 2015)
Kepler planet candidates require both spectroscopic and imaging follow-up observations to rule out false positives and detect blended stars. Traditionally, spectroscopy and high-resolution imaging have probed different host star companion parameter spaces, the former detecting tight binaries and the latter detecting wider bound companions as well as chance background stars. In this paper, we examine a sample of 11 Kepler host stars with companions detected by two techniques - near-infrared adaptive optics and/or optical speckle interferometry imaging, and a new spectroscopic deblending method. We compare the companion effective temperatures (Teff) and flux ratios (FB/FA, where A is the primary and B is the companion) derived from each technique and find no cases where both companion parameters agree within 1σ errors. In 3/11 cases the companion Teff values agree within 1σ errors, and in 2/11 cases the companion FB/FA values agree within 1σ errors. Examining each Kepler system individually considering multiple avenues (isochrone mapping, contrast curves, probability of being bound), we suggest two cases for which the techniques most likely agree in their companion detections (detect the same companion star). Overall, our results support the advantage that the spectroscopic deblending technique has for finding very close-in companions (θ ≲ 0.″02-0.″05) that are not easily detectable with imaging. However, we also specifically show how high-contrast AO and speckle imaging observations detect companions at larger separations (θ ≥ 0.″02-0.″05) that are missed by the spectroscopic technique, provide additional information for characterizing the companion and its potential contamination (e.g., position angle, separation, magnitude differences), and cover a wider range of primary star effective temperatures. The investigation presented here illustrates the utility of combining the two techniques to reveal higher-order multiples in known planet-hosting systems. © 2015. The American Astronomical Society. All rights reserved.
Keywords: binaries: general; dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: interferometric; techniques: photometric; techniques: spectroscopic

Four sub-Saturns with dissimilar densities: Windows into planetary cores and envelopes - Petigura, Erik A.; Sinukoff, Evan; Lopez, Eric D.; Crossfield, Ian J. M.; Howard, Andrew W.; Brewer, John M.; Fulton, Benjamin J.; Isaacson, Howard T.; Ciardi, David R.; Howell, Steve B.; Everett, Mark E.; Horch, Elliott P.; et al. (The Astronomical Journal, 2017)
We present results from a Keck/HIRES radial velocity campaign to study four sub-Saturn-sized planets, K2-27b, K2-32b, K2-39b, and K2-108b, with the goal of understanding their masses, orbits, and heavy-element enrichment. The planets have similar sizes (RP=4.5-5.5 ), but have dissimilar masses (MP=16-60 ), implying a diversity in their core and envelope masses. K2-32b is the least massive (MP = 16.5 ± 2.7 M) and orbits in close proximity to two sub-Neptunes near a 3:2:1 period commensurability. K2-27b and K2-39b are significantly more massive at MP = 30.9 ± 4.6 M and MP = 39.8 ± 4.4 M, respectively, and show no signs of additional planets. K2-108b is the most massive at MP = 59.4 ± 4.4 M, implying a large reservoir of heavy elements of about ≈50 . Sub-Saturns as a population have a large diversity in planet mass at a given size. They exhibit remarkably little correlation between mass and size; sub-Saturns range from ≈6-60 M, regardless of size. We find a strong correlation between planet mass and host star metallicity, suggesting that metal-rich disks form more massive planet cores. The most massive sub-Saturns tend to lack detected companions and have moderately eccentric orbits, perhaps as a result of a previous epoch of dynamical instability. Finally, we observe only a weak correlation between the planet envelope fraction and present-day equilibrium temperature, suggesting that photo-evaporation does not play a dominant role in determining the amount of gas sub-Saturns accrete from their protoplanetary disks. © 2017. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed; planets and satellites: composition; planets and satellites: detection; planets and satellites: dynamical evolution and stability; planets and satellites: formation; planets and satellites: gaseous planets; planets and satellites: interiors

Detection of planetary and stellar companions to neighboring stars via a combination of radial velocity and direct imaging techniques - Kane, Stephen R.; Dalba, Paul A.; Li, Zhexing; Horch, Elliott P.; Hirsch, Lea A.; Horner, Jonathan; Wittenmyer, Robert A.; Howell, Steve B.; Everett, Mark E.; Butler, R. Paul; Tinney, Christopher G.; Carter, Brad D.; et al. (The Astronomical Journal, 2019)
The sensitivities of radial velocity (RV) surveys for exoplanet detection are extending to increasingly longer orbital periods, where companions with periods of several years are now being regularly discovered. Companions with orbital periods that exceed the duration of the survey manifest in the data as an incomplete orbit or linear trend, a feature that can either present as the sole detectable companion to the host star, or as an additional signal overlain on the signatures of previously discovered companion(s). A diagnostic that can confirm or constrain scenarios in which the trend is caused by an unseen stellar rather than planetary companion is the use of high-contrast imaging observations. Here, we present RV data from the Anglo-Australian Planet Search (AAPS) for 20 stars that show evidence of orbiting companions. Of these, six companions have resolved orbits, with three that lie in the planetary regime. Two of these (HD 92987b and HD 221420b) are new discoveries. Follow-up observations using the Differential Speckle Survey Instrument (DSSI) on the Gemini South telescope revealed that 5 of the 20 monitored companions are likely stellar in nature. We use the sensitivity of the AAPS and DSSI data to place constraints on the mass of the companions for the remaining systems. Our analysis shows that a planetary-mass companion provides the most likely self-consistent explanation of the data for many of the remaining systems.
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: radial velocities

Observations of binary stars with the Differential Speckle Survey Instrument. VIII. Measures of metal-poor and triple stars from 2015 to 2018 - Horch, Elliott P.; Tokovinin, Andrei; Weiss, Samuel A.; Löbb, János; Casetti-Dinescu, Dana I.; Granucci, Nicole M.; Hess, Nicole M.; Everett, Mark E.; van Belle, Gerard T.; Winters, Jennifer G.; Nusdeo, Daniel A.; Henry, Todd J.; et al. (The Astronomical Journal, 2019)
We present 248 speckle observations of 43 binary and 19 trinary star systems chosen to make progress in two main areas of investigation: the fundamental properties of metal-poor stars and star formation mechanisms. The observations were taken at the Gemini North and South telescopes during the period 2015 July to 2018 April, mainly with the Differential Speckle Survey Instrument but also with a few early results from the new 'Alopeke speckle camera at Gemini North. We find that the astrometry and photometry of these observations as a whole are consistent with previous work at Gemini. We present five new visual orbits for systems important in understanding metal-poor stars, three of which have orbital periods of less than 4 yr, and we indicate the degree to which these and future observations can impact our knowledge of stellar properties and star formation. In particular, we find a decrease in mass at fixed spectral type for metal-poor stars versus their solar-metallicity analogs that is consistent with predictions that are made from current stellar models. © 2019. The American Astronomical Society. All rights reserved..
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: individual; techniques: high angular resolution; techniques: interferometric; techniques: photometric

K2 discovers a busy bee: an unusual transiting neptune found in the beehive cluster - Obermeier, Christian; Henning, Thomas; Schlieder, Joshua E.; Crossfield, Ian J. M.; Petigura, Erik A.; Howard, Andrew W.; Sinukoff, Evan; Isaacson, Howard; Ciardi, David R.; David, Trevor J.; Hillenbrand, Lynne A.; Beichman, Charles A.; et al. (The Astronomical Journal, 2016)
Open clusters have been the focus of several exoplanet surveys, but only a few planets have so far been discovered. The Kepler spacecraft revealed an abundance of small planets around small cool stars, therefore, such cluster members are prime targets for exoplanet transit searches. Kepler's new mission, K2, is targeting several open clusters and star-forming regions around the ecliptic to search for transiting planets around their low-mass constituents. Here, we report the discovery of the first transiting planet in the intermediate-age (800 Myr) Beehive cluster (Praesepe). K2-95 is a faint (Kp = 15.5 mag) dwarf from K2's Campaign 5 with an effective temperature of 3471 ±124 K, approximately solar metallicity and a radius of 0.402± 0.050.R⊕ We detected a transiting planet with a radius of3.47+0.78 -0.53R⊕ and an orbital period of 10.134 days. We combined photometry, medium/high-resolution spectroscopy, adaptive optics/speckle imaging, and archival survey images to rule out any false-positive detection scenarios, validate the planet, and further characterize the system. The planet's radius is very unusual as M-dwarf field stars rarely have Neptune-sized transiting planets. The comparatively large radius of K2-95b is consistent with the other recently discovered cluster planets K2-25b (Hyades) and K2-33b (Upper Scorpius), indicating systematic differences in their evolutionary states or formation. These discoveries from K2 provide a snapshot of planet formation and evolution in cluster environments and thus make excellent laboratories to test differences between field-star and cluster planet populations. © 2016. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; eclipses; peer-reviewed; stars: individual (K2-95); stars: low-mass; techniques: photometric; techniques: spectroscopic

Three temperate neptunes orbiting nearby stars - Fulton, Benjamin J; Howard, Andrew W; Weiss, Lauren M; Sinukoff, Evan; Petigura, Erik A; Isaacson, Howard; Hirsch, Lea A; Marcy, Geoffrey W; Henry, Gregory W; Grunblatt, Samuel K; Huber, Daniel; Huber, Daniel; et al. (The Astrophysical Journal, 2016)
We present the discovery of three modestly irradiated, roughly Neptune-mass planets orbiting three nearby Solartype stars. HD 42618 b has a minimum mass of 15.4±2.4 M⊕, a semimajor axis of 0.55 au, an equilibrium temperature of 337 K, and is the first planet discovered to orbit the solar analogue host star, HD 42618. We also discover new planets orbiting the known exoplanet host stars HD 164922 and HD 143761 (p CrB). The new planet orbiting HD 164922 has a minimum mass of 12.9±1.6 M⊕ and orbits interior to the previously known Jovian mass planet orbiting at 2.1 au. HD 164922 c has a semimajor axis of 0.34 au and an equilibrium temperature of 418 K. HD 143761 c orbits with a semimajor axis of 0.44 au, has a minimum mass of 25±2 M⊕, and is the warmest of the three new planets with an equilibrium temperature of 445 K. It orbits exterior to the previously known warm Jupiter in the system. A transit search using space-based CoRoT data and ground-based photometry from the Automated Photometric Telescopes (APTs) at Fairborn Observatory failed to detect any transits, but the precise, high-cadence APT photometry helped to disentangle planetary-reflex motion from stellar activity. These planets were discovered as part of an ongoing radial velocity survey of bright, nearby, chromospherically inactive stars using the Automated Planet Finder (APF) telescope at Lick Observatory. The high-cadence APF data combined with nearly two decades of radial velocity data from Keck Observatory and gives unprecedented sensitivity to both short-period low-mass, and long-period intermediate-mass planets. © 2016. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; planetary systems; stars: individual (HD 42618, HD 164922, HD 143761)

275 candidates and 149 validated planets orbiting bright stars in K 2 campaigns 0–10 - Mayo, Andrew W.; Vanderburg, Andrew; Latham, David W.; Bieryla, Allyson; Morton, Timothy D.; Buchhave, Lars A.; Dressing, Courtney D.; Beichman, Charles; Berlind, Perry; Calkins, Michael L.; Ciardi, David R.; Crossfield, Ian J. M.; et al. (The Astronomical Journal, 2018)
Since 2014, NASA's K2 mission has observed large portions of the ecliptic plane in search of transiting planets and has detected hundreds of planet candidates. With observations planned until at least early 2018, K2 will continue to identify more planet candidates. We present here 275 planet candidates observed during Campaigns 0-10 of the K2 mission that are orbiting stars brighter than 13 mag (in Kepler band) and for which we have obtained high-resolution spectra (R = 44,000). These candidates are analyzed using the vespa package in order to calculate their false-positive probabilities (FPP). We find that 149 candidates are validated with an FPP lower than 0.1%, 39 of which were previously only candidates and 56 of which were previously undetected. The processes of data reduction, candidate identification, and statistical validation are described, and the demographics of the candidates and newly validated planets are explored. We show tentative evidence of a gap in the planet radius distribution of our candidate sample. Comparing our sample to the Kepler candidate sample investigated by Fulton et al., we conclude that more planets are required to quantitatively confirm the gap with K2 candidates or validated planets. This work, in addition to increasing the population of validated K2 planets by nearly 50% and providing new targets for follow-up observations, will also serve as a framework for validating candidates from upcoming K2 campaigns and the Transiting Exoplanet Survey Satellite, expected to launch in 2018. © 2018. The American Astronomical Society. All rights reserved.
Keywords: dept.phy; methods: data analysis; peer-reviewed; planets and satellites: detection; techniques: photometric

HAT-P-58b – HAT-P-64b: Seven planets transiting bright stars - Bakos, G. Á.; Hartman, Joel D.; Bhatti, Waqas; Csubry, Z.; Penev, Kaloyan; Bieryla, Allyson; Latham, D. W.; Quinn, S. N.; Buchhave, Lars A.; Kovács, Gábor L.; Torres, Guillermo; Noyes, R. W.; et al. (The Astronomical Journal, 2021)
We report the discovery and characterization of seven transiting exoplanets from the HATNet survey. The planets, which are hot Jupiters and Saturns transiting bright Sun-like stars, include: HAT-P-58b (with mass M p = 0.37 M J, radius R p = 1.33 R J, and orbital period P = 4.0138 days), HAT-P-59b (M p = 1.54 M J, R p = 1.12 R J, P = 4.1420 days), HAT-P-60b (M p = 0.57 M J, R p = 1.63 R J, P = 4.7948 days), HAT-P-61b (M p = 1.06 M J, R p = 0.90 R J, P = 1.9023 days), HAT-P-62b (M p = 0.76 M J, R p = 1.07 R J, P = 2.6453 days), HAT-P-63b (M p = 0.61 M J, R p = 1.12 R J, P = 3.3777 days), and HAT-P-64b (M p = 0.58 M J, R p = 1.70 R J, P = 4.0072 days). The typical errors on these quantities are 0.06 M J, 0.03 R J, and 0.2 s, respectively. We also provide accurate stellar parameters for each of the host stars. With V = 9.710 0.050 mag, HAT-P-60 is an especially bright transiting planet host, and an excellent target for additional follow-up observations. With R p = 1.703 0.070 R J, HAT-P-64b is a highly inflated hot Jupiter around a star nearing the end of its main-sequence lifetime, and is among the largest known planets. Five of the seven systems have long-cadence observations by TESS which are included in the analysis. Of particular note is HAT-P-59 (TOI-1826.01) which is within the northern continuous viewing zone of the TESS mission, and HAT-P-60, which is the TESS candidate TOI-1580.01. © 2021. The American Astronomical Society. All rights reserved..
Keywords: dept.phy; peer-reviewed

197 candidates and 104 validated planets in k2's first five fields - Crossfield, Ian J M; Ciardi, David R; Petigura, Erik A; Sinukoff, Evan; Schlieder, Joshua E; Schlieder, Joshua E; Howard, Andrew W; Beichman, Charles A; Isaacson, Howard; Dressing, Courtney D; Christiansen, Jessie L; Fulton, Benjamin J; et al. (Astrophysical Journal Supplement Series, 2016)
We present 197 planet candidates discovered using data from the first year of the NASA K2 mission (Campaigns 0-4), along with the results of an intensive program of photometric analyses, stellar spectroscopy, high-resolution imaging, and statistical validation. We distill these candidates into sets of 104 validated planets (57 in multi-planet systems), false positives, and 63 remaining candidates. Our validated systems span a range of properties, with median values of RP= 2.3 R⊕, P = 8.6 days, Teff = 5300 K, and Kp = 12.7mag. Stellar spectroscopy provides precise stellar and planetary parameters for most of these systems. We show that K2 has increased by 30% the number of small planets known to orbit moderately bright stars (1-4 R R⊕, Kp = 9-13 mag). Of particular interest are planets smaller than 2 R⊕, orbiting stars brighter than Kp = 11.5 mag, 5 receiving Earth-like irradiation levels, and several multi-planet systems - including 4 planets orbiting the M dwarf K2-72 near mean-motion resonances. By quantifying the likelihood that each candidate is a planet we demonstrate that our candidate sample has an overall false positive rate of 15%-30%, with rates substantially lower for small candidates (<2R⊕) and larger for candidates with radii >8 R⊕ and/or with P<3 days. Extrapolation of the current planetary yield suggests that K2 will discover between 500 and 1000 planets in its planned four-year mission, assuming sufficient follow-up resources are available. Efficient observing and analysis, together with an organized and coherent follow-up strategy, are essential for maximizing the efficacy of planet-validation efforts for K2, TESS, and future large-scale surveys. © 2016. The American Astronomical Society. All rights reserved.
Keywords: catalogs; dept.phy; planets and satellites: fundamental parameters; planets and satellites: general; techniques: high angular resolution; techniques: photometric; techniques: spectroscopic